Centrosema (Centrosema pubescens) Leaf Meal as Protein Supplement for Pullet Chicks and Growing Pullets - Nworgu, F.C.; Fasogbon, F.O. (International Journal of Poultry Science, 2007)
The study was conducted to determine the optimum dietary inclusion rate of Cetrosema pubescens leaf meal (CLM) for pullet chicks (PC) and growing pullets (GP). Eighty four Black Nera pullet chicks were weighed and randomly allotted to four dietary treatments which contained 0, 2, 4 and 6% CLM for A, B, C and D, respectively in a completely randomized design. Treatment A served as control and each treatment was replicated 3 times. The PC experiment lasted for 6 weeks, while the GP experiment lated for 8 weeks i.e after 4 weeks of acclimatization after chicks experiment. The results revealed that inclusion of 2-6% CLM for PC did not have significant (P>0.05) effect on the mean body weight gain (MBWG), feed conversion ratio (FCR), protein efficiency ratio (PER) unlike feed and water intake. However, MBWG, FCR, PER and cost of feed per kilogram live weight gain (CFPKLING), for the GP were significantly (P